Unclear situational models for training of operators of ergatic control systems - Гузий, H. H. (Proceedings of National Aviation University (archive), 1998)
Questions of use of unclear situational models for training of operators of ergatic control systems are discussed. Structure imitation and situational functional training-tool of skills of making the decisions along with use of fuzzy models of evaluation of actions of the operator are offered